Complex space weather events of 2017 September - Hajra, Rajkumar; Tsurutani, Bruce T.; Lakhina, G.S. (My University, 2020)
Interplanetary coronal mass ejections (ICMEs), magnetic clouds (MCs), sheaths, corotating interaction regions (CIRs), solar wind high-speed streams (HSSs), fast forward shocks (FSs), reverse waves (RWs), stream interfaces, and heliospheric current sheet crossings detected upstream of the Earth and their geoeffectiveness are studied during 2017 September. The most intense geomagnetic storm (SYM-H peak = −146 nT) starting on September 7 had a three-step main phase. A compound interplanetary structure resulting from an FS encountering and compressing the upstream MC southward interplanetary magnetic fields (IMFs) caused the first two steps of the storm. A magnetospheric supersubstorm (SSS; SML peak = −3712 nT) led to the third and most intense step. An MC portion of an ICME created an intense storm (SYM-H peak = −115 nT) on September 8. A second SSS (SML peak = −2642 nT) occurred during the main phase of this storm. Intense geomagnetically induced currents (GICs) occurred during the SSSs. Two moderate magnetic storms with peak SYM-H indices of −65 and −74 nT occurring on September 13 and 27 were caused by sheath and CIR southward IMFs, respectively. Six FSs and their associated sheaths caused sudden impulses (SI+s) of magnitude ranging from +11 to +56 nT. The shocks/sheaths led to magnetospheric relativistic electron flux decreases. The RWs caused SI−s and substorm recoveries by reducing southward IMFs. The high-intensity long-duration continuous AE activities (HILDCAAs) caused by the HSSs were related to the increase/acceleration of relativistic electron fluxes.
Keywords: Solar flares; Solar coronal mass ejections; Corotating streams; Interplanetary shocks